Pemberdayaan Perempuan Berbasis Aset Individu dalam Meningkatkan Ekonomi Kreatif Desa Tulung Sampung Ponorogo melalui Pelatihan Pembuatan Produk Keterampilan dari Tali Kur - Ratnawati, Siti Rohmaturrosyidah (Proceedings of Annual Conference on Community Engagement, 2018)
Women everywhere including in Tulung Village Sampung Ponorogo, certainly have individual assets to do various productive and creative activities which can increase family income and also economic level of the village. But, unfortunately their individual assets often have not been managed well so that their role in increasing village’s economy rate was not optimal. So that, empowerment and accompaniment efforts for women in Tulung Sampung are needed to encourage the participation of women in all sectors of life, including economic strengthening programs. To realize it, students of community service at Tulung with the ABCD (Asset Based Community Development) method, facilitate the women empowerment program in Tulung by holding the training of making handycraft from cord rope such as bags, wallets and key chains. This agenda is intended to equip them with skills and improve their motivation and entrepreneurial mentality so that at the end, they can play a vital role in increasing the creative economy in the village of Tulung Sampung